Does optimal foraging theory explain the behavior of the oldest human cannibals?. Issue 131 (June 2019) - Rodríguez, Jesús; Guillermo, Zorrilla-Revilla; Ana, Mateos
Abstract: Cannibalism is an old and widespread human practice; however, the causes and meaning of consuming other humans are still hotly debated. Several explanations are possible for cannibalistic behavior, ranging from social and cultural motivations to purely nutritional causes. In this study, we analyze the oldest known case of cannibalism to date in the framework of the Optimal Foraging Theory (OFT). The fossil assemblage from the TD6.2 unit of the Gran Dolina site (Sierra de Atapuerca, Spain), dated to c. 0.9 Ma, includes the remains of several hominins ( Homo antecessor ) with unquestionable signs of cannibalism and a large collection of fossils of other mammals, also with evidence of human consumption. The Optimal Foraging Theory predicts that foragers confronted with a number of options aim to maximize their return rate, obtaining the maximum benefit with the minimum cost. We estimated the nutrient caloric return and the cost of acquisition of humans and other large mammals in TD6.2, and evaluated the rank of hominins among all the food resources harvested by H. antecessor using a Prey Choice Model (PreyCM). We also show that the abundance of the different prey types represented in the TD6.2 assemblage is proportional to the abundance of those resources in the environment, a prediction of the OFT. Although TD6.2 assemblage fits the predictions of the PreyCM, humans are overrepresented with respect to their estimated abundance in the environment. This overrepresentation of hominins was likely due to a higher encounter rate, as may be expected if the cannibalized individuals belonged to the same group as the foragers, although other explanations are possible. The results presented here show that hominins were a high-ranked prey type and, thus, their inclusion in the diet of H. antecessor is predicted by the OFT.